Affirmative actions in terms of special rights: Confronting structural violence in Brazilian higher education - Gomes da Silva, Guilherme Henrique; Skovsmose, Ole [UNESP] (Sage Publications Ltd, 2019)
In this article, the authors interpret affirmative actions with reference to structural violence, which is accompanied by legitimizing discourses that tend to make discrimination appear natural and unquestionable. They illustrate the extension of structural violence in Brazilian society with particular reference to access to higher education. It has been common to talk about some groups of students as having special needs. However, the authors see groups of students suffering structural violence as being groups with special rights, and explore affirmative actions through the notion of special rights. The authors find that special-rights terminology establishes the discussion of affirmative actions in higher education in a broader and, at the same time, more profound conceptual framework related to interpretations of social justice. Simultaneously, special-rights terminology brings an educational specificity to the discussion of affirmative actions. Thus, the authors see affirmative actions as being both a general sociopolitical and specific educational challenge.
Keywords: Affirmative actions; higher education; structural violence; special rights; educational specificity; critical mathematics education